Answer:
Explanation:
1 ) Given that
![(d^2y/dx^2) + 4y = x - x^2 + 20\\\\ (d^2y/dx^2) + 4y = - x^2 + x + 20](https://img.qammunity.org/2021/formulas/mathematics/college/ycnozk4vp3lmrneckrg2xfvnozosdzc2u0.png)
For a non homogeneous part
, we assume the particular solution is
![y_p(x) = Ax^2 + Bx + C](https://img.qammunity.org/2021/formulas/mathematics/college/wpcz2ts6a93zv9kladl8anivlcuv3yvm06.png)
2 ) Given that
![d^2y/dx^2 + 6dy/dx + 8y = e^(2x)](https://img.qammunity.org/2021/formulas/mathematics/college/lgp97t3r0rq9rna4tchefsztn4jx011xo0.png)
For a non homogeneous part
, we assume the particular solution is
![y_p(x) = Ae^(2x)](https://img.qammunity.org/2021/formulas/mathematics/college/mx2hfwjhn8f6dw5s67h0kjwb5tqkz6tt1j.png)
3 ) Given that
y′′ + 4y′ + 20y = −3sin(2x)
For a non homogeneous part −3sin(2x) , we assume the particular solution is
![y_p(x) = Acos(2x)+Bsin(2x)](https://img.qammunity.org/2021/formulas/mathematics/college/x2xjrw3uvoixasrg82gdr4agdlrnwbz4lv.png)
4 ) Given that
y′′ − 2y′ − 15y = 3xcos(2x)
For a non homogeneous part 3xcos(2x) , we assume the particular solution is
![y_p(x) = (Ax+B)cos2x+(Cx+D)sin2x](https://img.qammunity.org/2021/formulas/mathematics/college/m7a72rwf6dxn43amegv3xnsafd1qbxu38z.png)